The relationship between physician burnout and quality of healthcare in terms of safety and acceptability: a systematic review - Sarah Bonato; Carolyn S Dewa; Desmond Loong; Lucy Trojanowski (BMJ Open)
Objectives This study reviews the current state of the published peer-reviewed literature related to physician burnout and two quality of care dimensions. The purpose of this systematic literature review is to address the question, ‘How does physician burnout affect the quality of healthcare related to the dimensions of acceptability and safety?’Design Using a multiphase screening process, this systematic literature review is based on publically available peer-reviewed studies published between 2002 and 2017. Six electronic databases were searched: (1) MEDLINE Current, (2) MEDLINE In-process, (3) MEDLINE Epub Ahead of Print, (4) PsycINFO, (5) Embase and (6) Web of Science.Setting Physicians practicing in civilian settings.Participants Practicing physicians who have completed training.Primary and secondary outcome measures Quality of healthcare related to acceptability (ie, patient satisfaction, physician communication and physician attitudes) and safety (ie, minimising risks or harm to patients).Results 4114 unique citations were identified. Of these, 12 articles were included in the review. Two studies were rated as having high risk of bias and 10 as having moderate risk. Four studies were conducted in North America, four in Europe, one in the Middle East and three in East Asia. Results of this systematic literature review suggest there is moderate evidence that burnout is associated with safety-related quality of care. Because of the variability in the way patient acceptability-related quality of care was measured and the inconsistency in study findings, the evidence supporting the relationship between burnout and patient acceptability-related quality of care is less strong.Conclusions The focus on direct care-related quality highlights additional ways that physician burnout affects the healthcare system. These studies can help to inform decisions about how to improve patient care by addressing physician burnout. Continued work looking at the relationship between dimensions of acceptability-related quality of care measures and burnout is needed to advance the field.